TOG‘LI HUDUDLARDA TURIZM VA REKREATSIYA XO‘JALIGINI RIVOJLANTIRISHNING BA’ZI MASALALARI - Jumaev, T.J.; Qurbonov, Sh.B.; Xamdamov, E.D. (SCIENCE and SOCIETY, 2023)
The article considers some geographical aspects of the development of tourism and recreation in mountainous areas. Also, based on the available theoretical and practical information, directions, conclusions and recommendations for the socio-economic development of mountain regions are given.